First Session of the House of Representatives under the Constitution of the Republic of Iraq for 2005: An analytical study - طالب مصدق عادل (Journal of Legal Sciences, 2019)
The purpose of this study is to handle the constitutional and legal arrangement of the first session of the House of Representatives in Iraq, whether the procedural and objective aspects. the study also handle the practical problems associated with this session and its implications in relation to determining the mandate of the Council of Representatives, the President of the Republic and the Council of Ministers. The study reviewed the position of some of the Iraqi and comparison constitutions of the first session of the parliament, and determine the previous or contemporary or subsequent procedures to hold the first session, and it compares the theoretical constitutional reality with the practical political reality in order to give an integrated asset of the process formation of constitutional institutions, and handling the impact of violation of these provisions.